2020
DOI: 10.1080/0284186x.2020.1753889
|View full text |Cite
|
Sign up to set email alerts
|

A national study to assess outcomes of definitive chemoradiation regimens in proximal esophageal cancer

Abstract: Background: Proximal esophageal cancer (EC) is commonly treated with definitive chemoradiation (CRT). The radiation dose and type of chemotherapy backbone are still under debate. The objective of this study was to compare the treatment outcomes of contemporary CRT regimens. Material and Methods: In this retrospective observational cohort study, we included patients with locally advanced squamous cell cancer of the proximal esophagus, from 11 centers in the Netherlands, treated with definitive CRT between 2004 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…Patients were identified in site-specific databases, complemented with the Netherlands Cancer Registry, a population-based cancer registry of all newly diagnosed malignancies in the Netherlands. We identified 200 consecutive patients who underwent definitive CRT for proximal EC, from January 2004 to December 2014 [15]. All patients had histologically confirmed SCC of the proximal esophagus, with maximum distal extension up to 24 cm of the incisors, in which supraclavicular nodal involvement was allowed.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Patients were identified in site-specific databases, complemented with the Netherlands Cancer Registry, a population-based cancer registry of all newly diagnosed malignancies in the Netherlands. We identified 200 consecutive patients who underwent definitive CRT for proximal EC, from January 2004 to December 2014 [15]. All patients had histologically confirmed SCC of the proximal esophagus, with maximum distal extension up to 24 cm of the incisors, in which supraclavicular nodal involvement was allowed.…”
Section: Methodsmentioning
confidence: 99%
“…Since the TNM classification did not essentially change, no coding was performed to a uniform TNM version, except nodal status which was converted into N1 excluding subdivision of N1/2/3. Further information on the study protocol was described previously [15].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Twenty‐three percent of patients with SCLNM who received chemoradiotherapy and/or had resection were still alive after 3 years. The 3‐year survival rate was higher in previous studies of patients with esophageal cancer who had received definitive chemoradiotherapy (36%‐46%) 5,21 . A population‐based study of the CROSS regimen reported 5‐year survival rates of 62% and 38%, depending on response after neoadjuvant chemoradiotherapy 22 .…”
Section: Discussionmentioning
confidence: 90%
“…The 3-year survival rate was higher in previous studies of patients with esophageal cancer who had received definitive chemoradiotherapy (36%-46%). 5,21 A population-based study of the CROSS regimen reported 5-year survival rates of 62% and 38%, depending on response after neoadjuvant chemoradiotherapy. 22 Similarly, survival after definitive chemoradiotherapy predominantly depended on response, with complete responders showing a 3-year survival rate of 58%.…”
Section: Discussionmentioning
confidence: 99%